Highly cytotoxic agents from luvunga scandens against human breast adenocarcinoma Cell Line (MCF7) - Al-Zikri, Putri Nur Hidayah; Bakhtiar, M. Taher; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari (2014)

(untitled)
Breast cancer is among of the frequently diagnosed cancer and major of death in the most of country in the world. These led to the necessity for the development of potential chemotherapeutic agents against breast cancer cells with novel mechanisms of actions. The plant-derived triterpeniods commonly used due to its ability to exhibit cytotoxicity against a variety of tumor cells [1]. Luvunga scandens plant (Rutaceae) is one of the plant-derived triterpenoids were responsible to use in this study. In order to investigate the cytotoxicity effect of L. scandens plant, extractions and it isolated compound were derived and assayed on human breast adenocarcinoma cell line (MCF-7). The stems of L. scandens were extracted with n-hexane, dichloromethane (DCM) and ethanol (EtOH). DCM extracts were then further fractionated by vacuum liquid chromatography (VLC) into five extracts; namely n-hexane, n-hexane:DCM, DCM, DCM:MeOH and MeOH. Those five extracts were assayed in vitro cytotoxic activity against MCF-7. Among them, DCM:MeOH fraction was found to be the most effective and was further subjected to isolation procedure and the isolated compound was assayed in vitro cytotoxic activity against MCF-7. Bioactivity-guided fractionation of the fraction through successive column chromatography procedures led to the isolation of a triterpenes-type of compound. A comparison of NMR data showed an appropriate match with the previously reported data. The structure of the compound was elucidated to be lanosta-8, 24-dien-21-oicacid, 3-oxo, (13a, 14b, 17a, 20S)-, a well-known triterpenes with molecular formula C30H46O3. This compound was found to be responsible for the cytotoxicity effects with the half maximal inhibitory concentration (IC50) value 24.8 μM. Whereas IC50 of DCM extract and DCM: MeOH fraction extract is 75 µg/mL and 94 µg/mL respectively. This basic study, therefore, revealed that L. scandens plants are potential sources of cytotoxic agents.